The use of fluorine-18 fluorodesoxyglycose-positron emission tomography for treatment monitoring in patients with soft tissue sarcomas - Kasper, Bernd; Hohenberger, Peter; Strauss, Ludwig G.; Dimitrakopoulou-Strauss, Antonia (Hellenic journal of nuclear medicine, 2010)
Positron emission tomography (PET) using 2-deoxy-2-[(18)F] fluoro-D-glucose ((18)F-FDG) has been used with increased frequency in the care of patients with soft tissue sarcomas to predict malignant potential of tumours, prognosis of survival and response to chemotherapy. Although there are several other PET tracers, which have found limited use in sarcomas, this review focuses on the use of (18)F-FDG, which is the most common used tracer. Recent literature and developments covering major aspects of PET imaging in the management of patients with soft tissue sarcomas will be discussed in this review with focus on treatment monitoring. Positron emission tomography cannot be used instead of histology to diagnose sarcomas, but may aid in biopsy planning. In particular, using the last generation PET/computerized tomography (CT) scanners, it is easily possible to combine morphological information provided by CT and/or magnetic resonance imaging with biological information based on PET. Imaging with PET has been shown to detect accurately primary tumours as well as lymph node and bone metastases in patients with sarcomas. In soft tissue sarcomas, changes in tumour (18)F-FDG uptake correlate significantly with histopathological response, risk of tumour recurrence and survival. In conclusion, PET is emerging as an important imaging modality in the management of patients with soft tissue sarcomas.
Der Artikel hat keine eigene Startseite
Gesehen am 07.03.2023